A multi-scale approach for the discovery of zeolites for hydrogen sulfide removal. (4th August 2016) - Liu, Tingting; First, Eric L.; Faruque Hasan, M.M.; Floudas, Christodoulos A.
Abstract : Highlights: Discovery of zeolites with reverse adsorption selectivities for H2 S removal. Detailed process modeling and optimization for adsorption-based H2 S removal. Identified the most cost-effective zeolites for H2 S removal using PSA. Minimized total investment and operating costs. Novel use of shape-, pore- and size-selectivities for zeolite screening. Abstract: Removing H2 S from industrial gases is important to avoid operational hazards and to meet environmental regulation. Microporous zeolites are potential adsorbents for separating H2 S from other gases. While large number of candidate zeolites exists, it is not trivial to select cost-effective zeolites capable of satisfying process constraints and specifications. In this work, a novel method for the zeolite-based H2 S separation is put forward which pertains to a multi-scale modeling, simulation, and optimization framework for combined material screening and process optimization to reduce the overall process cost. The framework spans the atomistic and mesoscopic scales for the screening and selection of zeolites and the macroscopic scale for the simulation and selection of optimal conditions for pressure swing adsorption (PSA)-based H2 S separation technology. Applying this framework, several novel zeolites have been identified for the first time for separation of H2 S from representative H2 S/CO2, H2 S/N2, and H2 S/CH4 mixtures. The zeolites which are screened are capable of removing H2 S from natural gas, acid gas, tail gas, flue gas, refinery gas, biogas, landfill gas, and other gases of industrial importance. Results show that it is possible to perform cost-effective H2 S removal by exploiting reverse selectivity of the gas molecules using novel micro-porous materials. We have also identified zeolite ABW as an adsorbent with high potential for commercialization for multi-purpose gas separation including acid gas removal from natural gas and carbon capture from power plants.